(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study was necessitated by persistent declining in the academic achievement in Basic Technology in public examinations by junior secondary school students. The study determined the effects of cooperative learning method (CLM) on academic achievement and retention in Basic Technology in Oyo State. Three research questions guided the study and three null hypotheses were tested at 0.05 level of significance. The population of the study was 19,892 JSS II Basic Technology students in Oyo State. The purposive sampling technique was used to select 114 students for the study. Pre-test, Post-test and non-equivalent group quasi-experimental research design was used for the study and the instrument for data collection was Basic Technology Achievement Test (BTAT) which was validated by three experts. A reliability correlation coefficient of 0.82 was obtained for the test items using test retest and Pearson Product Moment Correlation. Mean was used to analyse data relating to the research questions while analysis of covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. Findings revealed that students taught Basic Technology using CLM performed better with higher post-test scores than those taught using conventional teaching method (CTM). Findings also indicated that retention mean score of students taught Basic Technology using CLM was higher than those taught using CTM, both high and low achieving students were favoured by the use of CLM but low achieving students were slightly favoured by the use of CLM but low achieving students were slightly favoured more. The interaction effect of teaching methods and gender was not significant on students’ academic achievement and retention in Basic Technology. Hence, it was recommended among others that school administrators should provide opportunities for in-service training for Basic Technology teachers in order to equip them with competencies needed in the use of CLM for teaching the subject.